Nanoparticulate Nickel-Hosting Phases in Sulfidic Environments: Effects of Ferrous Iron and Bacterial Presence on Mineral Formation Mechanism and Solid-Phase Nickel Distribution - Mansor, Muammar; Winkler, Christopher; Hochella, Michael F.; Xu, Jie (Frontiers in Earth Science, 2019)
The precipitation of nickel with sulfide is an important process governing the bioavailability of Ni in natural waters, and this process has the potential to effectively remove aqueous Ni contaminants in near-surface environments. In this study, we use experimental approaches to investigate the diversity of Ni-hosting phases precipitated in sulfidic environments across a range of aqueous Ni-to-Fe ratios ([Ni]aq/[Fe]aq) and in the presence or absence of the sulfate-reducing bacteria (SRB), Desulfovibrio vulgaris. In the absence of Fe(II), the initial precipitates in abiotic experiments are found to consist primarily of polyphasic Ni-sulfides (average sizes < 20 nm) with millerite (trigonal NiS) cores and amorphous shells. The precipitates’ crystallinity is enhanced noticeably over a period of ~6 days, forming larger-sized hexagonal α-NiS, and observations of defects such as twinning and stacking faults implicate a formation pathway via reassembly of fine nanoparticulate precursors. By comparison, in the presence of SRB and in the absence of Fe, more crystalline phases such as polydymite (Ni3S4) and vaesite (NiS2) are also precipitated in addition to the monosulfide phases. The observed difference suggests that the presence of SRB enables the transformation of polyphasic precursors to more crystalline structures through the combined effects of bacterial metabolites and localized precipitation within a low pH micro-environment around the cell walls. The addition of Fe(II) (i.e., [Ni]aq/[Fe]aq = 5:1) leads to formation of less crystalline Ni-sulfides in both biotic and abiotic systems, indicating crystal structure distortion caused by substitution of Ni with Fe. With decreasing [Ni]aq/[Fe]aq, Ni-sulfides become rarer, mixed Ni-Fe phases start to appear, and finally Ni-rich mackinawite (FeS) becomes the primary Ni-hosting phase at the lowest ratio tested ([Ni]aq/[Fe]aq = 1:5). We propose that whether aqueous Ni forms discrete Ni-S phases or is incorporated into dominantly Fe-S phases is primarily determined by the precipitation kinetics, and our experiments at [Ni]aq/[Fe]aq = 1:1 suggest that Ni-sulfide precipitation kinetics is comparable or higher than Fe-sulfides at this condition. Overall, our study allows for prediction on the phases and biogeochemical factors controlling Ni removal and availability in sulfidic environments.